Teachers’ and postgraduate nursing students’ experience of the educational environment in Iran: A qualitative Research - Fatemeh Hajihosseini (Electronic Physician, 2017)
Background: The learning environment has a significant role in determining nursing students' academic achievements and course satisfaction. Creating a proper educational environment is therefore necessary for improving the quality of teaching and learning, and for delivering competent graduates to society. Objective: The present study was conducted to explore teachers' and postgraduate nursing students’ experience of the educational environment in Iran. Methods: This qualitative study uses an inductive approach and conventional content analysis. Data were collected through semi-structured face-to-face interviews with seven PhD students, seven faculty members (directors) and two focus groups comprising of fourteen master’s students in total, selected from three major universities in Tehran, Iran. Results: Seven subcategories were extracted from the data, including the organizational context, interactive climate, teachers’ competency, student appreciation, research centeredness, educational guidance and professionalism. Conclusion: The educational environment of postgraduate nursing programs in Iran encompasses different dimensions that can serve as both key points for educational environment evaluators and as guidelines for officials at different levels, to modify the weaknesses and improve the strengths of the system.